Membrane Filtration and Desiccation for Optimization of Urine Concentration - Singh, Gurmukh; Bollag, Roni J (Archives of Clinical and Biomedical Research, 2025)
Background: For urine immunofixation electrophoresis a 100-fold urine concentration is recommended. This is not always feasible. Based on prior findings, we considered whether lack of optimal concentration of urine may have resulted in missing pathogenic monoclonal light chains in some urine specimens. Methods: Membrane filtration urine concentration provides a 25-fold concentration. Residual urine was further concentrated by desiccation to achieve higher-fold concentration for 170 specimens that were negative for monoclonal light chains following membrane filtration concentration. Immunofixation electrophoresis was repeated after further concentration by desiccation. Data from previous observations were reevaluated to assess the importance of native urine protein concentration. Results: Of the 170 specimens subjected to further concentration by desiccation, monoclonal kappa light chains were detected in one specimen that was negative by the routine method. The most common probable explanation for discordant results in multiple specimens from a given patient, in the earlier report, was low urine protein concentration. Conclusions: While it would be ideal to achieve 100-fold concentration of urine for immunofixation electrophoresis, a 25-fold concentration has a minimal failure rate. We recommend that if the native urine protein concentration is <20 mg/dL, further concentration by desiccation should be applied to membrane filtration-concentrated urine specimens to avoid potential false negative result.